Abrocitinib: a potential treatment for moderate-to-severe atopic dermatitis. (1st September 2020) - Nezamololama, Novin; Crowley, Erika L.; Gooderham, Melinda J.; Papp, Kim
ABSTRACT: Introduction: Atopic dermatitis (AD) is a common and debilitating dermatosis that often impacts the physical and psychological quality of life in children and adults. A limited number of treatment options are available for AD, and often these treatments result in an insufficient response or may be contraindicated for some patients. This treatment gap creates an increasing demand for alternative AD therapies. The Janus kinase (JAK)-signal transducers and activators of transcription (STAT) pathway is known to play a critical role in the dysregulation of immune responses in AD. Inhibition of the JAK enzymes in the JAK-STAT pathway has shown potential for the treatment of this chronic skin condition. Areas covered: We review the evolving efficacy and safety profile of abrocitinib, an oral JAK1 inhibitor, in the treatment of AD based on the data available from phase I, II, and III clinical trials. Expert opinion: Evidence supports clinical efficacy, improved pruritus and an acceptable safety profile, making abrocitinib a viable alternative to conventional AD therapies. Pivotal phase III trials included subjects aged 12 years and above, providing a new mechanism of action for future treatment of adolescent and adult AD. Further investigations are required to have a thorough understanding of abrocitinib in the treatment of AD.